Cephalometric assessment of Colombia’s mestizo population aged 6 to 12 years - Pedro María Jaramillo-Vallejo (Universidad de Antioquia, 2020)
Introduction: over the years, populations have been studied by means of lateral cephalic x-rays in a variety of ethnicities, ages, and study types, setting standards for different groups. In Latin America, studies show cephalometric differences from standards based on Caucasian populations. Method: 1,627 cases of patients without prior treatment were analyzed; the sample included 855 males and 772 females aged 6 to 12 years. Lateral cephalic radiographs and specific tracing were taken. Descriptive analysis was done using mean, standard deviation, minimum, and maximum. Comparisons were made between male and female subjects and by age. Results: a greater size was found in all measurements in male subjects, being statistically significant in some measurements and ages. The ages with the most differences were 8 and 9 years, and the least difference occurred at the age of 10. Conclusion: there was variation in maxillary and mandibular size with age and gender, with the largest size in males and indications of vertical predominance.